Peran Lembaga Sosial terhadap Perkembangan Agribisnis di Kelurahan Rurukan Kecamatan Tomohon Timur - Arini Pamona; Jen Tatuh; Paulus A. Pangemanan; Agnes E. Loho (COCOS, 2015)
ABSTRACTArini Pamona, The Role of Social Institution to the Development of Agribusiness in Rurukan, Eastern District of Tomohon, supervised by Prof. Dr. Ir. Jen Tatuh, MS as Chief, Dr. Ir. Paulus A. Pangemanan, MS and Dr. Ir. Agnes E. Loho, MP as members.This study aimed to assess the role of the Social Organization of the Agribusiness Development in Sub Rurukan Eastern District of Tomohon. The benefits of this research is to provide information about the Role of Social Institutions of the Agribusiness Development in Sub Rurukan Eastern District of Tomohon and provide knowledge / insight to those who need this information. The collection of data, in the form of primary data and secondary data. Primary data through direct interviews based on a list of questions that have been prepared and secondary data derived from other sources associated with this research (BPS). Snowball sampling method using the method. Initial information obtained from Village which is a Key Person, community / religious leaders, continue to the next until the informant met with all information needed. Number of respondents were 12 respondents, which consists of four community leaders / religious leaders and each institution 1 board and 1 member. The results showed that each agency plays in each sub-system. Farmers Group acts by 50% in the provision of the means of production and agricultural tools and machines in the sub-system Agriindustri Hulu, Mapalus and Ma'rawis role of 100% in the supply of labor in sub-system Agriproduksi, Farmers Group acts by 10% in the processing of agricultural products be finished / semi-finished (Agro-Industry) on Agriindustri downstream sub-system, and the United Farmers Group / Arisan contribute by 75% in the delivery of information / education, technology, the provision of capital (financial / credit) as well as human resources development in the sub-system Agriservis, while sub Agriniaga system is not supported by social institutions. The overall role of social institutions can be said to contribute good but not very good because there is still a sub-system that has not been supported by social institutions, namely sub-systems Agriniaga resulting imbalance in this system.Key words: Social Institutions, Agribusiness, Eastern Tomohon